Найди корень уравнения 3(y + 5) + 5(2y – 3) = 4(y – 9)и вычисли значение выражения –0,5y – 2
Ответы на вопрос
Ответил jekadva
54
Ответ:
Пошаговое объяснение:
3(y + 5) + 5(2y – 3) = 4(y – 9)
3y + 15 + 10y - 15 = 4y - 36
13y = 4y - 36
13y - 4y = -36
9y = -36
y = -36 : 9
y = -4
========
–0,5y – 2 = -0,5 * (-4) - 2 = 2 - 2 = 0
Новые вопросы
Окружающий мир,
1 год назад
Литература,
6 лет назад
Қазақ тiлi,
6 лет назад
История,
8 лет назад
Математика,
8 лет назад
3y + 15 + 10y - 15 = 4y - 36
13y = 4y - 36
13y - 4y = -36
9y = -36
y = -36 : 9
y = -4
========
–0,5y – 2 = -0,5 * (-4) - 2 = 2 - 2 = 0